PENGARUH ZAKAT TERHADAP PEREKONOMIAN MASYARAKAT JAWA TIMUR (TINJAUAN INDEX ZAKAT NASIONAL) - Iit Mazidah; Arivatu Ni'mati Rahmatika (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2021)
Indonesia is a country that has the largest Muslim population in the world and is included in the top 10 countries with economic power. Macroeconomics is the concept that wealth and income must be distributed equally, so as to increase GRDP that can touch all levels of society, especially people with absolute poverty levels. So that the quality of economic growth can be felt by all levels of society, the increase in GRDP must be followed by a reduction in the number of reductions and weather. This study uses quantitative panel data analysis using Fixed effect model analysis. The data panel used uses management and zakat data from BAZNAS in East Java and GRDP in East Java. The purpose of this study was to determine the effect of zakat funds on indicators of economic welfare of the people of East Java. From the results of the study, it was found that zakat funds had a positive effect but did not significantly affect the economy of the people of East Java.